2013
DOI: 10.1007/s40299-013-0145-2
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Instructional Effectiveness to Reveal Its Relationship to Learning

Abstract: The purpose of the present study is to define instructional profiles and investigate the relationship between these profiles and learning indicators such as endof-semester grades and self-reported amount of learning. Instructional profiles were obtained using a segmentation method. Student ratings were used as indicators of instructional effectiveness. Results revealed that instructors who receive higher scores from students seem to be effective instructors in learning. However, instructors with high ratings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The main reason for this is because what SET forms measure, i.e., instructional effectiveness, is a multifaceted trait. Kalender (2014) found that different groups have varying definitions of instructional effectiveness based on SET forms. A similar study by Young and Shaw (1999) also defined different instructional profiles based on students' responses to SET forms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for this is because what SET forms measure, i.e., instructional effectiveness, is a multifaceted trait. Kalender (2014) found that different groups have varying definitions of instructional effectiveness based on SET forms. A similar study by Young and Shaw (1999) also defined different instructional profiles based on students' responses to SET forms.…”
Section: Introductionmentioning
confidence: 99%
“…Additional support came from studies by Trivedi, Pardos and Heffernan (2011) and Marsh and Hocevar (1991) who identified several subgroups of students showing distinct characteristics different than whole body. Furthermore, it was shown that subgroups students might exhibit varying behaviours in SET forms (Kalender, 2014;Smith & Cranton, 1992;Tenenbaum, 1977). It was the existence of such groups with varying responses to SET items that motivated the researcher to study on invariance of SET forms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, another cluster which included classes with low reliabilities was shown to have strong construct validity. Indeed unfitting models were expected since, as Young and Shaw (1999) and Kalender (2014), showed that there is no universal definition of instructional effectiveness acceptable for all. Thus it can be said that when confronted with low reliabilities, checking construct validity should be step which is needed to be checked.…”
Section: Relationship Between Reliability and Validitymentioning
confidence: 99%